Pemberdayaan Siswa Sekolah Dasar Dalam Pencegahan Kecacingan Di Kota Kupang - Christine J K Ekawati; Wanti; Siprianus Singga; Edwin Mauguru (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2023)
Worms are caused by human behavior. Types of worms that are often the cause of worms are hookworn and Trichuris trichiura. Until now there are still school-age children who are infected by Soil Transmitted Helminth (STH), but public awareness to prevent and deal with helminthiasis is still lacking. Due to the ignorance of the community, especially students and teachers, the school must prepare facilities for washing hands and soap that meet the requirements so that children after playing or before eating at school wash their hands first and the risk of worm infection can decrease. The method used is counseling and training. The results obtained from 14 respondents who took part in this Abdimas activity were at the time of the pretest as many as 57.14% of respondents knew about intestinal worms and their prevention. After being given counseling and training, the results increased to 73.21%. This means that the level of knowledge of respondents about worms rose 16.07%. Through this Abdimas students participate in the socialization of helminthiasis in the environment where they are located, namely at school, at home and in the surrounding environment.